2019
DOI: 10.1111/jcmm.14786
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SPRY4‐IT1 regulates breast cancer cell stemness through competitively binding miR‐6882‐3p with TCF7L2

Abstract: SPRY4‐intronic transcript 1 has been found in several kinds of cancers, but the role of SPRY4‐IT1 in breast cancer stem cells has not been studied. We investigated whether SPRY4‐IT1 is involved in the promotion of breast cancer stem cells (BCSCs). We used qRT‐PCR to detect the expression of SPRY4‐IT1 in MCF‐7 cells and MCF‐7 cancer stem cells (MCF‐7 CSCs). The effects of SPRY4‐IT1 on the proliferation and renewal ability of breast cancer cells were investigated by in vitro and in vivo assays (ie in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…MiRNA sponge is a crucial role of lncRNAs. Recent years, increasing studies have revealed that lncRNAs can regulate tumor progression by sequestering miRNAs thus releasing their downstream target mRNAs and prompting mR-NAs to exert functions [22][23][24]. Here, we applied bioinformatics analysis to screen out the miRNAs that potentially interact with FGD5-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA sponge is a crucial role of lncRNAs. Recent years, increasing studies have revealed that lncRNAs can regulate tumor progression by sequestering miRNAs thus releasing their downstream target mRNAs and prompting mR-NAs to exert functions [22][23][24]. Here, we applied bioinformatics analysis to screen out the miRNAs that potentially interact with FGD5-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…Promotes stemness by sequestering miR-6882-3p which targets TCF4, allowing initiation of canonical Wnt signaling [76]. [76] miR-6882-3p…”
Section: Spry4-it1mentioning
confidence: 99%
“…SPRY4-IT1 is an intronic lncRNA transcribed from one of the introns of the SPRY4 gene, which encodes a tumor suppressor [102]. SPRY4-IT1 is upregulated in CD44 high CD24 low ER+ MCF-7 cells and expression of stemness factors OCT4, c-Myc, NANOG and SOX2 are positively correlated with SPRY4-IT1 expression levels [76]. Further analysis revealed that SPRY4-IT1 mediates its stemness promoting effects by acting as a ceRNA to sequester miR-6882-3p [76], which targets TCF7L2/TCF4.Thus, SPRY4-IT1 promotes stemness by promoting the Wnt/β-catenin signaling pathway.…”
Section: Spry4-it1mentioning
confidence: 99%
“…The ceRNA (competitive endogenous RNA) hypothesis believes that a large-scale transcriptional regulatory network may be formed between RNAs, which can affect biological processes [23]. Our study is based on the ceRNA hypothesis, that is, cbr3-as1 directly binds to miR-25-3p, thus targeting JNK1 / MEK4, activating MAPK pathway, and ultimately affecting the chemoresistance process of BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was carried out according to the method mentioned in the previous study [23]. We collected BRCA tissues of patients from the First A liated Hospital of China Medical University for ISH assay.…”
Section: Ish (In Situ Hybridization) and Ihc (Immunohistochemistry)mentioning
confidence: 99%